Possíveis relações entre elementos meteorológicos e a epidemiologia espaço-temporal da dengue e malária no Estado do Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2013)
The incidence of vector-borne diseases currently appearing as a major public health problem. The life cycle of disease vectors such as malaria and dengue, are influenced by environmental characteristics of the site. In the Amazon region, precipitation is the largest component of weather variability can act in different form in the spatial distribution of these diseases vector. Accordingly, the objective of this study was to analyze the incidence of dengue and malaria in seven municipalities of Pará located in regions with different amounts of annual rainfall. Using correlation and regression analysis, it was found that precipitation acts differently in the incidence of dengue and malaria in different locations. Spatially, it was found that the location in different volumes of annual rainfall was decisive to justify the differences in the incidences of these diseases in municipalities. Temporally, dengue and malaria exhibited a heterogeneous distribution among municipalities and varied over the years in major and minor transmission, even in years influenced by ENSO. Seasonally, it was found that dengue occurred in the rainy season while in the dry malaria.
Keywords: Dengue; Malária; Precipitação; CNPQ::CIÊNCIAS EXATAS E DA TERRA; INTERAÇÃO BIOSFERA ATMOSFERA